2012
DOI: 10.5194/gmd-5-919-2012
|View full text |Cite
|
Sign up to set email alerts
|

MAESPA: a model to study interactions between water limitation, environmental drivers and vegetation function at tree and stand levels, with an example application to [CO<sub>2</sub>] × drought interactions

Abstract: Abstract.Process-based models (PBMs) of vegetation function can be used to interpret and integrate experimental results. Water limitation to plant carbon uptake is a highly uncertain process in the context of environmental change, and many experiments have been carried out that study drought limitations to vegetation function at spatial scales from seedlings to entire canopies. What is lacking in the synthesis of these experiments is a quantitative tool incorporating a detailed mechanistic representation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 112 publications
0
126
0
1
Order By: Relevance
“…A stem conductance k p = 4 mmol H 2 O m −2 s −1 MPa −1 gives a whole-plant conductance k L = 2 mmol H 2 O m −2 s −1 MPa −1 for moist soil with neglibile soil resistance, if root and stem conductances are equal. Duursma and Medlyn (2012) Ollinger et al (2008). c Estimated using empirical relationships between N area and V cmax25 from the TRY leaf trait database (Kattge et al, 2009) with observed foliage N converted from N mass to N area using the mean leaf mass per unit area (LMA) for temperate forest trees reported in the Glopnet leaf trait database (Wright et al, 2004).…”
Section: Plant Hydraulic Conductancementioning
confidence: 99%
“…A stem conductance k p = 4 mmol H 2 O m −2 s −1 MPa −1 gives a whole-plant conductance k L = 2 mmol H 2 O m −2 s −1 MPa −1 for moist soil with neglibile soil resistance, if root and stem conductances are equal. Duursma and Medlyn (2012) Ollinger et al (2008). c Estimated using empirical relationships between N area and V cmax25 from the TRY leaf trait database (Kattge et al, 2009) with observed foliage N converted from N mass to N area using the mean leaf mass per unit area (LMA) for temperate forest trees reported in the Glopnet leaf trait database (Wright et al, 2004).…”
Section: Plant Hydraulic Conductancementioning
confidence: 99%
“…The MAESPA model (Duursma and Medlyn 2012) coupled the soil water balance components of the SPA model (Williams et al 1996) to the MAESTRA model (Medlyn 2004), with some major changes and additions. MAESTRA was a 3D single-tree and stand process-based model that calculated light interception and distribution within crowns and used a leaf physiology submodel to estimate photosynthesis and transpiration.…”
Section: Maespa Presentationmentioning
confidence: 99%
“…The computational efficiency of 3D PBMs can be improved by representing individual tree crowns as simple shapes such as ellipsoids or cones (e.g., MAESTRA model, Medlyn 2004; MAE-SPA model, Duursma and Medlyn 2012). Such models, however, require a larger set of parameters than stand-scale PBMs, thus limiting their use in forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been developed to simulate interactions for light, water, and nutrients between trees and crops (Charbonnier et al, 2013;Duursma and Medlyn, 2012;van Noordwijk and Lusiana, 1999;Talbot, 2011) or to predict tree growth and crop yield in agroforestry systems (Graves et al, 2010;. However, none of these models are designed to simulate SOC dynamics in agroforestry systems and they are therefore not useful to estimate SOC storage.…”
mentioning
confidence: 99%